CAR T-Cells in Multiple Myeloma: State of the Art and Future Directions - Luis Gerardo Rodríguez-Lobato (Frontiers in Oncology, 2020)
Despite recent therapeutic advances, the prognosis of multiple myeloma (MM) patients remains poor. Thus, new strategies to improve outcomes are imperative. Chimeric antigen receptor (CAR) T-cell therapy has changed the treatment landscape of B-cell malignancies, providing a potentially curative option for patients who are refractory to standard treatment. Long-term remissions achieved in patients with acute lymphoblastic leukemia and Non-Hodgkin Lymphoma encouraged its further development in MM. B-cell maturation antigen (BCMA)-targeted CAR T-cells have established outstanding results in heavily pre-treated patients. However, several other antigens such as SLAMF7 and CD44v6 are currently under investigation with promising results. Idecabtagene vicleucel is expected to be approved soon for clinical use. Unfortunately, relapses after CAR T-cell infusion have been reported. Hence, understanding the underlying mechanisms of resistance is essential to promote prevention strategies and to enhance CAR T-cell efficacy. In this review we provide an update of the most recent clinical and pre-clinical data and we elucidate both, the potential and the challenges of CAR T-cell therapy in the future.